Anisotropy of (partial) isothermal remanent magnetization: DC-field-dependence and additivity. Issue 2 (17th May 2019) - Biedermann, Andrea R; Jackson, Mike; Bilardello, Dario; Feinberg, Joshua M
SUMMARY: Anisotropy of isothermal remanent magnetization (AIRM) is useful for describing the fabrics of high-coercivity grains, or alternatively, the fabrics of all remanence-carrying grains in rocks with weak remanence. Comparisons between AIRM and other measures of magnetic fabric allow for description of mineral-specific or grain-size-dependent fabrics, and their relation to one another. Additionally, when the natural remanence of a rock is carried by high-coercivity minerals, it is essential to isolate the anisotropy of this grain fraction to correct paleodirectional and paleointensity data. AIRMs have been measured using a wide range of applied fields, from a few mT to several T. It has been shown that the degree and shape of AIRM can vary with the strength of the applied field, for example, due to the contribution of separate grain subpopulations or due to field-dependent properties. To improve our understanding of these processes, we systematically investigate the variation of AIRM and the anisotropy of partial isothermal remanence (ApIRM) with applied field for a variety of rocks with different magnetic mineralogies. We also test the additivity of A(p)IRMs and provide a definition of their error limits. While A(p)IRM principal directions can be similar for a range of applied field strengths on the same specimen, the degree and shape of anisotropy often show systematic changes with the field over which the (p)IRM was applied. Also, the data uncertainty varies with field window; typically, larger windows lead to better-defined principal directions. Therefore, the choice of an appropriate field window is crucial for successful anisotropy corrections in paleomagnetic studies. Due to relatively large deviations between AIRMs calculated by tensor addition and directly measured AIRMs, we recommend that the desired A(p)IRM be measured directly for anisotropy corrections.